Description of a new species of Cosmolaelaps Berlese and the male of C. brevipedestra (Karg) from Iran, with notes on some other species of Cosmolaelaps Berlese (Acari: Laelapidae) - Nemati, Alireza; Gwiazdowicz, Dariusz J. (Zootaxa, 2016)
We describe a new species of mite, Cosmolaelaps malmiriensis sp. nov., based on morphological characters of the adult female. We also describe the male of C. brevipedestra (Karg, 1985) and re-describe its female. Gaeolaelaps angustiscutatus (Willmann, 1951), and Gymnolaelaps markewitschi (Pirianyk, 1959) are transferred into Cosmolaelaps. Cosmolaelaps acutiscutus Teng, 1982 and C. subacutiscutus Bai & Wang, 2005 appear to be junior synonyms of C. angustiscutatus. Cosmolaelaps confinisetarum Moreira et al., 2014 is synonymised with C. guttulata (Karg, 1978).